2005
DOI: 10.1302/0301-620x.87b5.15602
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of posterior cruciate ligament-retaining and -substituting total knee arthroplasty

Abstract: We performed a prospective, randomised trial of 44 patients to compare the functional outcomes of a posterior-cruciate-ligament-retaining and posterior-cruciate-ligament-substituting total knee arthroplasty, and to gain a better understanding of the in vivo kinematic behaviour of both devices. At follow-up at five years, no statistically significant differences were found in the clinical outcome measurements for either design. The prevalence of radiolucent lines and the survivorship were the same. In a subgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
170
2
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(203 citation statements)
references
References 51 publications
30
170
2
1
Order By: Relevance
“…Studies on tibial internal-external rotation after TKA have reported mixed findings, with some researchers noting decreases [45] and others reporting no change [12]. We observed an increase in tibial rotation, but our average value for the native condition is similar to what Siston et al [45] reported for osteoarthritic knees (4.9°± 4.1°) and nearly identical to what Victor et al [52] observed for TKA knees (10.8°).…”
Section: Discussionsupporting
confidence: 84%
“…Studies on tibial internal-external rotation after TKA have reported mixed findings, with some researchers noting decreases [45] and others reporting no change [12]. We observed an increase in tibial rotation, but our average value for the native condition is similar to what Siston et al [45] reported for osteoarthritic knees (4.9°± 4.1°) and nearly identical to what Victor et al [52] observed for TKA knees (10.8°).…”
Section: Discussionsupporting
confidence: 84%
“…PCL substitution in primary TKA has traditionally relied on a cam and post (cam-post) mechanism in the form of a posterior-stabilized (PS) design. Short-and long-term evaluations of PS and CR knees have failed to show clinically significant differences in their outcomes [2,11,12,[17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Also, in vivo kinematic studies involving patients undergoing TKA have documented reverse rotational patterns [2,10] and lateral condylar liftoff [13,21,34,37]. There is evidence these abnormal kinematic patterns lead to decreased ROM [3,11,38]. In addition, these abnormal kinematic patterns possibly relate to inferior functional performance of daily activities by patients undergoing TKA.…”
Section: Introductionmentioning
confidence: 99%
“…In the spectrum of kinematic abnormalities, a couple studies suggest subjects having a posterior stabilized (PS) TKA have less abnormal knee kinematics in deeper flexion and greater flexion than subjects having a posterior cruciate-retaining (PCR) TKA [8,38]. However, measurement in weightbearing conditions typically reduces the observed ROM [11].…”
Section: Introductionmentioning
confidence: 99%